Development of polypropylene-based composites through fused filament fabrication: The effect of carbon-based fillers. (January 2023) - Casamento, Francesco; Padovano, Elisa; Pappalardo, Stefano; Frache, Alberto; Badini, Claudio
Highlights: PP composites reinforced with carbonaceous fillers were developed using FFF. Filaments of each material were processed, and a viable FFF process was optimized. The effect of fillers was evaluated in terms of materials' thermo-physical properties. The addition of fillers led to improvements of mechanical properties of FFF samples. Abstract: Fused Filament Fabrication (FFF) is the most widespread additive manufacturing technique for polymeric materials. However, only a limited number of materials are available to be processed through this technique. Polypropylene and its composites are extremely versatile materials which are employed in a wide range of applications, but their use in FFF has not been much investigated due to issues related to adhesion and warping. In this work, composites having polypropylene as matrix and different carbonaceous fillers, namely carbon nanotubes and carbon fibers, were developed using FFF. Compounding, filament extrusion and FFF processes were successfully developed and optimized for each material. The materials were characterized in terms of their thermo-physical properties and the effect of the fillers on these properties was investigated. The addition of carbon fibers led to a significant improvement of mechanical properties, and a more moderate increase was observed in the case of carbon nanotubes addition.